2019
DOI: 10.1159/000505003
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Glucocorticoid-Induced Leucine Zipper Peptide Inhibits Lipopolysaccharide-Induced Ocular Inflammation in Rats

Abstract: To demonstrate the anti-inflammatory action of a synthetic glucocorticoid-induced leucine zipper (GILZ 98-134) peptide (GILZ-p) in a model of endotoxin-induced uveitis (EIU) in rats. Methods: The EIU model was induced in Sprague Dawley rats with an intravitreal injection of lipopolysaccharide (LPS). Synthetic GILZ-p was injected intravitreally 6 h after the LPS injection. To evaluate the anti-inflammatory effects of GILZ-p, the inflammatory response in the anterior chamber and iris of the rat eyes was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Glucocorticoid-induced leucine zipper (GILZ) is a gene rapidly transcribed by either endogenous or pharmacologically administered glucocorticoids [ 1 , 2 , 3 , 4 , 5 ]. Several studies have demonstrated that GILZ exerts anti-inflammatory activity, often acting as a mediator of glucocorticoid actions but without the glucocorticoid-derived side effects [ 6 , 7 , 8 , 9 , 10 ]. While almost ubiquitously expressed, GILZ is rapidly induced by glucocorticoids primarily in immune cells of the adaptive and innate system and regulates their cellular functions (e.g., activation, differentiation, and apoptosis) [ 3 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoid-induced leucine zipper (GILZ) is a gene rapidly transcribed by either endogenous or pharmacologically administered glucocorticoids [ 1 , 2 , 3 , 4 , 5 ]. Several studies have demonstrated that GILZ exerts anti-inflammatory activity, often acting as a mediator of glucocorticoid actions but without the glucocorticoid-derived side effects [ 6 , 7 , 8 , 9 , 10 ]. While almost ubiquitously expressed, GILZ is rapidly induced by glucocorticoids primarily in immune cells of the adaptive and innate system and regulates their cellular functions (e.g., activation, differentiation, and apoptosis) [ 3 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another proof of the efficacy of GILZ-based peptides is given by the use of a synthetic TAT-GILZ peptide (GILZ-p) in a model of ocular uveitis in rats. The inflammatory response was counteracted by the intravitreal injection of GILZ-p, which could reduce the expression of IL-1β and TNF-α ( 86 ).…”
Section: Discussion: Gilz-based Proteins As Potential Pharmacologicalmentioning
confidence: 99%
“…The animal model with infected eyes was set up by an injection of LPS/PS solution (0.2 mg/ml) into the anterior chamber (Guo et al, 2019). The incision was made in the cornea margin of rabbits to allow the aqueous humor to flow naturally.…”
Section: In Vivo Anti-inflammatory Assessmentmentioning
confidence: 99%